Reproduction, Smell, and Neurodevelopmental Disorders: Genetic Defects in Different Hypogonadotropic Hypogonadal Syndromes - Valdes-Socin, Hernan; Rubio Almanza, Matilde; Tomé Fernández-Ladreda, Mariana; Debray, François Guillaume; Bours, Vincent; Beckers, Albert (Frontiers in Endocrinology, 2014)
The neuroendocrine control of reproduction in mammals is governed by a neural hypothalamic network of nearly 1500 gonadotropin-releasing hormone (GnRH) secreting neurons that modulate the activity of the reproductive axis across life. Congenital hypogonadotropic hypogonadism (HH) is a clinical syndrome that is characterized by partial or complete pubertal failure. HH may result from inadequate hypothalamic GnRH axis activation, or a failure of pituitary gonadotropin secretion/effects. In man, several genes that participate in olfactory and GnRH neuronal migration are thought to interact during the embryonic life. A growing number of mutations in different genes are responsible for congenital HH. Based on the presence or absence of olfaction dysfunction, HH is divided in two syndromes: HH with olfactory alterations [Kallmann syndrome (KS)] and idiopathic hypogonadotropic hypogonadism (IHH) with normal smell (normosmic IHH). KS is a heterogeneous disorder affecting 1 in 5000 males, with a three to fivefold of males over females. KS is associated with mutations in KAL1, FGFR1/FGF8, FGF17, IL17RD, PROK2/PROKR2, NELF, CHD7, HS6ST1, FLRT3, SPRY4, DUSP6, SEMA3A, NELF, and WDR11 genes that are related to defects in neuronal migration. These reproductive and olfactory deficits include a variable non-reproductive phenotype, including sensorineural deafness, coloboma, bimanual synkinesis, craniofacial abnormalities, and/or renal agenesis. Interestingly, defects in PROKR2, FGFR1, FGF8, CHD7, DUSP6, and WDR11 genes are also associated with normosmic IHH, whereas mutations in KISS1/KISSR, TAC3/TACR3, GNRH1/GNRHR, LEP/LEPR, HESX1, FSHB, and LHB are only present in patients with normosmic IHH. In this paper, we summarize the reproductive, neurodevelopmental, and genetic aspects of HH in human pathology.